2020
DOI: 10.1177/0846537120914894
|View full text |Cite
|
Sign up to set email alerts
|

Role of Various DW MRI and DCE MRI Parameters as Predictors of Malignancy in Solid Pulmonary Lesions

Abstract: Purpose: We aimed to evaluate various diffusion and dynamic contrast-enhanced magnetic resonance imaging (DCE MRI) parameters in differentiating malignant from benign pulmonary lesions. Methods: We enrolled 31 (22 males) patients who had solid pulmonary lesion(s) >2 cm in our cross sectional study. Of these, 23 (74.2%) were found to be malignant on histopathology. Dynamic contrast-enhanced MRI was performed using 36 dynamic measurements (volumetric interpolated breath-hold examination). Diffusion-weighted M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…IVIM perfusion-related D star and f values did not demonstrate a good diagnostic efficacy for differentiating malignant SPLs from benign SPLs, consistent with most previous studies 6 , 18 , 19 , but not the same as the studies conducted by Deng et al 20 and Wang et al 21 . The inconsistencies between these studies may be associated with the diverse pathological types included in each study and the poor measurement reproducibility of D star and f. Ultimately, D star and f values could be used to obtain tissue perfusion information without the injection of contrast agents, and this possibility should be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…IVIM perfusion-related D star and f values did not demonstrate a good diagnostic efficacy for differentiating malignant SPLs from benign SPLs, consistent with most previous studies 6 , 18 , 19 , but not the same as the studies conducted by Deng et al 20 and Wang et al 21 . The inconsistencies between these studies may be associated with the diverse pathological types included in each study and the poor measurement reproducibility of D star and f. Ultimately, D star and f values could be used to obtain tissue perfusion information without the injection of contrast agents, and this possibility should be confirmed in future studies.…”
Section: Discussionsupporting
confidence: 88%
“…Our study found that diffusion-related parameters derived from TSE-IVIM-DWI, D, and ADC values could distinguish between malignant and benign SPLs and possess higher diagnostic accuracy than D star and f, consistent with most lung DWI studies using echo planar–based acquisition techniques 18 , 19 . Furthermore, the AUC of D was slightly higher than that of ADC total , followed by ADC 800 .…”
Section: Discussionsupporting
confidence: 85%
“…In our study, The ADC min value was significantly higher among benign lesions compared to malignant ones (1.45 ± 0.5 vs. 0.99 ± 0.26) with cutoff point < 1.34 yielding sensitivity 56.3%, specificity 100%. Jiang et al [15], Kumar et al [16] and study results also reported that the ADC min in malignant pulmonary lesions were significantly lower than benign lesions.…”
Section: Discussionmentioning
confidence: 84%
“…It can noninvasively evaluate benign and malignant lung diseases and aid in pathological classification, grading, TNM stage, efficacy, and prognosis of lung cancer ( 5 ). A variety of MR functional imaging technologies, such as dynamic contrast-enhanced (DCE) ( 6 ), diffusion weighted imaging (DWI) ( 7 ), intravoxel incoherent motion (IVIM) ( 8 ) and diffusion kurtosis imaging (DKI) ( 9 ), can not only show the morphological characteristics of lung lesions but also obtain functional information, such as internal diffusion and perfusion of lung lesions, to provide important information on tissue function, physiology, pathology and molecules, which has important significance for guiding clinical individualized precision diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%